Suppression of endothelial ceramide de novo biosynthesis by Nogo-B contributes to cardiometabolic diseases - Luisa Rubinelli; Onorina Laura Manzo; Jin Sungho; Ilaria Del Gaudio; Rohan Bareja; Alice Marino; Sailesh Palikhe; Vittoria Di Mauro; Mariarosaria Bucci; Domenick J. Falcone; Olivier Elemento; Baran Ersoy; et al. (Nature Communications, 2025)
Abstract Accrual of ceramides, membrane and bioactive sphingolipids, has been implicated in endothelial dysfunction preceding cardiometabolic diseases. Yet, direct in vivo evidence, underlying mechanisms, and pathological implications are lacking. Here we show that suppression of ceramides and sphingosine-1-phosphate (S1P), a product of ceramide degradation, are causally linked to endothelial dysfunction and activation, contributing to vascular and metabolic disorders in high fat diet fed (HFD) male mice. Mechanistically, the upregulation of Nogo-B and ORMDL proteins suppress ceramide de novo biosynthesis in endothelial cells (EC) of HFD mice, resulting in vascular and metabolic dysfunctions. Systemic and endothelial specific deletion of Nogo-B restore sphingolipid signaling and functions, lowers hypertension, and hepatic glucose production in HFD. Our results demonstrate in vivo that ceramide and S1P suppression rather than accrual contributes to endothelial dysfunction and cardiometabolic diseases in HFD mice. Our study also sets a framework for the development of therapeutic strategies to treat these conditions